2012
DOI: 10.1002/jbm.a.34029
|View full text |Cite
|
Sign up to set email alerts
|

Bone turnover markers correlate with implant fixation in a rat model using LPS‐doped particles to induced implant loosening

Abstract: Revision surgery for particle-induced implant loosening in total joint replacement is expected to increase dramatically over the next few decades. This study was designed to investigate if local tissue and serum markers of bone remodeling reflect implant fixation following administration of lipopolysaccharide (LPS)-doped polyethylene (PE) particles in a rat model. 24 rats received bilateral implantation of intramedullary titanium rods in the distal femur, followed by weekly bilateral intra-articular injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 51 publications
(124 reference statements)
4
45
0
Order By: Relevance
“…A second limitation is that we did not include animal studies in which biomarkers of aseptic loosening/osteolysis were studied [14,18,21,27] because only two of these studies included stable and loosened implants [18,27]. These two studies showed dramatic increases in serum CTX-1, OPG, cathepsin K, and PINP and depression of serum OC.…”
Section: Discussionmentioning
confidence: 99%
“…A second limitation is that we did not include animal studies in which biomarkers of aseptic loosening/osteolysis were studied [14,18,21,27] because only two of these studies included stable and loosened implants [18,27]. These two studies showed dramatic increases in serum CTX-1, OPG, cathepsin K, and PINP and depression of serum OC.…”
Section: Discussionmentioning
confidence: 99%
“…19 A third scenario uses a larger hand drill with a 2.0 mm drill bit to widen the distal 5 mm of the ablation site, followed by implant placement. 20 This widened portion of the canal and the lack of bone wax allow for exposure of the ablation site to the joint space and is used in a model where particles are introduced into the joint space to mimic particle-induced peri-implant osteolysis. 20 Suturing and surgical staple placement are completed in the same manner as in the mouse surgery.…”
Section: Intramembranous Bone Regeneration and Implant Placement MM Mmentioning
confidence: 99%
“…4,17,20,21,37,38 To assess the reproducibility of the model, we re-analyzed outcome data from the mouse marrow ablation model and the rat implant fixation model in which the animal strain, age, sex and experimental end points were comparable. Both mouse studies included females from FVB/NJ and BALB/cJ strains of the same age (10-11 weeks) with the same end point (bone volume/tissue volume, BV/TV) at 7 days post-marrow ablation.…”
Section: Reproducibility Of Surgery Outcomesmentioning
confidence: 99%
See 2 more Smart Citations